1997
DOI: 10.1016/s0014-5793(97)00843-0
|View full text |Cite
|
Sign up to set email alerts
|

Natural hidden antibodies reacting with DNA or cardiolipin bind to thymocytes and evoke their death

Abstract: Both free and hidden natural antibodies to DNA or cardiolipin were obtained from immunoglobulins of a normal donor. The free antibodies reacting with DNA or cardiolipin were isolated by means of affinity chromatography. Antibodies occurring in an hidden state were disengaged from the depleted immunoglobulins by ion-exchange chromatography and were then affinity-isolated on DNA or cardiolipin sorbents. We used flow cytometry to study the ability of free and hidden antibodies to bind to rat thymocytes. Simultane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
0
6
0
2
Order By: Relevance
“…These have included both IgG and IgM Ab reactive with diverse antigens such as histones, DNA [16,17], myoglobin, pyruvate dehydrogenase, laminin, insulin, actin, ribosomal P proteins, and vimentin [18][19][20]. Similar to the IgG aPL described here, some of these have been found to be masked by their antigen [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These have included both IgG and IgM Ab reactive with diverse antigens such as histones, DNA [16,17], myoglobin, pyruvate dehydrogenase, laminin, insulin, actin, ribosomal P proteins, and vimentin [18][19][20]. Similar to the IgG aPL described here, some of these have been found to be masked by their antigen [21].…”
Section: Discussionmentioning
confidence: 99%
“…Their functions include the recognition of self constituents [12] or the elimination of effete cells [9,23]. Alternatively, they may serve as templates upon which antigen-driven selection generates specific Ab [24], while some NAA have clear effector functions [16] and pathogenetic potential [25]. Recent findings in the causation of apoptosis by autoantibody penetration into living cells may also indicate a primary role of NAA in the selection of the ultimate autoreactive cell repertoire [26].…”
Section: Discussionmentioning
confidence: 99%
“…In the blood of healthy donors natural hidden autoantibodies were found -antibodies that form complexes with antigens and antiidiotypic Abs. Hidden IgG and IgM to a wide range of cellular antigens [12] including intracellular molecules (DNA, cardiolipin, actin, pyruvate dehydroge nase), secreted molecules (serotonin, dopamine), mem brane, and extracellular components (phospholipids, col lagen, transferrin) have been found [13,14]. Moreover, specific IgAs to cardiolipin and DNA [13] have been detected.…”
Section: Hidden Antibodies In Blood Of Healthy Donorsmentioning
confidence: 99%
“…Hidden IgG and IgM to a wide range of cellular antigens [12] including intracellular molecules (DNA, cardiolipin, actin, pyruvate dehydroge nase), secreted molecules (serotonin, dopamine), mem brane, and extracellular components (phospholipids, col lagen, transferrin) have been found [13,14]. Moreover, specific IgAs to cardiolipin and DNA [13] have been detected. It was shown that antiidiotypic antibodies to IgM, IgG, and IgA can play the role of inhibitors mask ing hidden auto Abs in the blood of healthy donors [13,15].…”
Section: Hidden Antibodies In Blood Of Healthy Donorsmentioning
confidence: 99%
“…Так, для больных системной красной волчанкой (СКВ) и лимфопролиферативными заболеваниями харак терным является присутствие в крови ДНК-связывающих аутоАТ двух изотипов -IgG и IgM, отличающихся специ фичностью, степенью авидности и связывающими характе ристиками [8,9,10]. В повседневной клинической практике ДНК-абзимы, обладающие аналогично ДНК-связывающей аутоАТ специфичностью в весьма широких пределах, со храняют на определенном промежутке времени своего рода "функциональный нейтралитет, ускользая" от внимания клинициста [22,25,26]. Необходимость понимания клинической значимости ДНК-абзимов при системных аутоиммунных заболеваниях определила актуальность настоящих исследований.…”
unclassified